The role of transport costs and trade liberalisation in territorial competitiveness - Alejandra Trejo (European Regional Science Association (ERSA), 2010)
As a result of the advancement of globalisation and the increasing emphasis on competitiveness as a means to get a position in a globalised economy, the territory has regained a key role as a unit for analysis and action. In the context of the globalization local and regional territories compete to attract and retain productive investment and resources and increase its share in total production because it is at the territorial level that the benefits of external integration and the continuous improvement of well-being and abundance are expressed. Transport and trade costs are one dimension of competitiveness. Poor transport infrastructure, long transportation times, inefficiencies, etc. create significant costs which affect the ability of producers to access regional and international markets more quickly and effectively. An analysis of the role played by transport infrastructure and related costs in the development of competitiveness and productivity of regions is fundamental. Although transportation can become a determining factor in how the territory functions development also depends on other crucial factors such as the quality of institutions, economic policies and often openness to trade. This paper will assess the influence of a number of economic forces related to transport costs and trade liberalization on the geographic distribution of manufacturing in Mexico which is a country that carried out and intense process of liberalizations from the 1980's. We will employ GDP data at the state level (1970-2004) in an examination of regional densities in manufacturing as a dependent variable in a reduced form model, where proxies for trade costs and liberalisation are the explanatory variables. The econometric test will provide evidence on the role of interregional differences of transport costs, import access and FDI to foster agglomeration of economic activity which is a reflection of a region's competitiveness. Additionally we look for support for the argument that trade brings increasing agglomeration of economic activity in countries with poor infrastructure and high internal transport costs, as in the case of Mexico compared to industrialised economies.
Keywords: 330; Trade costs; Regional disparities; Competitiveness; Mexican manufacturing